2006
DOI: 10.1111/j.1440-1843.2006.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Sputum bacteriology in hospitalized patients with acute exacerbation of chronic obstructive pulmonary disease in Taiwan with an emphasis on Klebsiella pneumoniae and Pseudomonas aeruginosa

Abstract: Klebsiella pneumoniae and P. aeruginosa are the most common sputum pathogens in hospitalized patients with AECOPD in Taiwan, with the former being more commonly isolated from mild COPD and the latter associated with poor clinical outcome. These results should be considered when deciding which antibiotics should initially be used to treat patients with AECOPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
42
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 30 publications
12
42
1
6
Order By: Relevance
“…Furthermore, quantitative analysis of sputum culture showed good concordance with the bronchoscopic PSB results [26]. This finding supports the use of sputum with quantitative analysis as an easy method to procure a non-invasive form of sample and was used in various studies [12,13,27].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, quantitative analysis of sputum culture showed good concordance with the bronchoscopic PSB results [26]. This finding supports the use of sputum with quantitative analysis as an easy method to procure a non-invasive form of sample and was used in various studies [12,13,27].…”
Section: Discussionsupporting
confidence: 62%
“…Lin et al [27] reported high prevalence of infection with K. pneumoniae (19.6%) and P. aeruginosa (16.8%) among hospitalized patients of AE-COPD. However, the isolation of Klebsiella was predominated in mild COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In acute infective exacerbations, Enterobacteriaceae and Pseudomonas species predominate in patients with FEV1 ≤35% of the predicted value [13]. Potential pathogenic microorganisms reported from Taiwan in acute exacerbation of COPD were K pneumoniae (19.6%), P aeruginosa (16.8%), and H influenza (7.5%), followed by A baumannii (6.9%), Enterobacter species (6.1%), and Staphylococcus aureus (6.1%) [12]. In the current study; P aeruginosa, A baumannii, and K pneumoniae were the common pathogens for pneumonia; and P aeruginosa, H influenza, and K pneumoniae were the common pathogens for bronchitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, these pathogenic organisms may differ with severity of COPD, repeated exacerbation, current antibiotic use in 3 months and common pathogens at the respective admitting center [11,12]. Several reports have suggested that in patients with advanced stages of COPD and with severe exacerbation, Gram-negative bacilli (including Pseudomonas aeruginosa) were more common [12,13].…”
Section: W Reechaipichitkulmentioning
confidence: 99%
“…3) Development of COPD is slow and progressive in humans, with occasional exacerbations caused by an inflammatory response to triggering substances such as noxious gases, 1) bacteria [4][5][6] or viruses. [7][8][9][10][11] Four abnormalities are present in chronic, stable COPD: emphysema, small airway remodeling, pulmonary hypertension, and chronic bronchitis.…”
mentioning
confidence: 99%